Isokinetic knee joint evaluation in track and field events - Deli, C. K.; Paschalis, V.; Theodorou, A. A.; Nikolaidis, M. G.; Jamurtas, A. Z.; Koutedakis, Y. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to evaluate maximal torque of the knee flexors and extensors, flexor/extensor ratios, and maximal torque differences between the 2 lower extremities in young track and field athletes. Forty male track and field athletes 13-17 years old and 20 male nonathletes of the same age participated in the study. Athletes were divided into 4 groups according to their age and event (12 runners and 10 jumpers 13-15 years old, 12 runners and 6 jumpers 16-17 years old) and nonathletes into 2 groups of the same age. Maximal torque evaluation of knee flexors and extensors was performed on an isokinetic dynamometer at 60°/s. At the age of 16-17 years, jumpers exhibited higher strength values at extension than did runners and nonathletes, whereas at the age of 13-15 years, no significant differences were found between events. Younger athletes were weaker than older athletes at flexion. Runners and jumpers were stronger than nonathletes in all relative peak torque parameters. Nonathletes exhibited a higher flexor/extensor ratio compared with runners and jumpers. Strength imbalance in athletes was found between the 2 lower extremities in knee flexors and extensors and also at flexor/extensor ratio of the same extremity. Young track and field athletes exhibit strength imbalances that could reduce their athletic performance, and specific strength training for the weak extremity may be needed.